AEGIS, the Virtual European Genebank: Why it is such a good idea, why it is not working and how it could be improved - Hintum, Theo van; Engels, Johannes M.M.; Maggioni, Lorenzo (MDPI, 2021)
In this opinion paper, the authors describe the principles of the decentralized European virtual genebank (AEGIS) and analyze the reasons for its lack of success and why the European Cooperative Programme for Plant Genetic Resources (ECPGR) has not been able to improve this situation so far signiﬁcantly. Possible changes for making AEGIS a success, or at least steps in the right direction, are proposed. These changes center around the creation of a system of certiﬁed genebanks with proper quality management, guaranteeing the long-term conservation of, and immediate access to the plant genetic resources conserved in it.